Modern media technology transformation of social and communicative space - Margarita Sowa; Dyenizhna Svetlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
Disclosed is a communicative and technological potential of media technology in the transformation of social and communicative space; described classification characteristics GR-technologies; the possibilities of technology "transmedia storytelling" in attracting the target audience to interact in mixed reality, combining online and offline communication; analyzed signs phygital-tech, formed at the intersection of physical and digital reality, the potential of which is a combination of existing reality and virtual reality, as well as the transformation of communication, and consciousness of people, changing meanings and patterns of social communications. It is noted that the tools of modern media technologies should be integrated into conventional technologies that involve the emergence of innovations in social and communicative space.